Impact of Renewable Energy Sources Consumption on Economic Growth in Europe and Asia-Pacific Region - Viktorovna, Filimonova Irina; Yurievich, Nemov Vasily; Viktorovna, Provornaya Irina; Mikhailovna, Ozhogova Lyubov (International Journal of Energy Economics and Policy, 2021)
Renewable energy sources have a significant impact on transforming the world fuel and energy balance structure, exacerbating inter-fuel competition. The development of green energy and a low-carbon economy is a priority task of modern energy and foreign economic policy in many countries. However, the consumption of renewable energy is uneven. This is due to the high cost of technologies and equipment and certain «distrust» in alternative fuels and their capabilities. In a framework of this study, the authors evaluated the impact of renewable energy sources on the economic development of Europe and the Asia-Pacific region, which are the primary consumers of these types of energy. The article investigates the dependence of GDP growth on the growth in consumption of fossil and renewable energy sources both in aggregate form and individual types of energy. The detailed calculations made it possible to identify the degree of influence of renewable energy on the economy in several macro-regions and determine the most significant types of energy resources. This statistically confirmed the positive impact of wind energy in Europe and solar energy in the Asia-Pacific region. The obtained regression estimates confirm the positive influence and stimulating effect of renewable energy on Europe and the Asia-Pacific region. The results obtained by the authors are based on data for the period from 1990 to 2017. Keywords: renewable energy sources, fossil fuel, hydrocarbons, economic growth, Europe, Asia-Pacific region, panel data analysis. JEL Classifications: C23, C33, Q2, Q21, Q43. DOI: https://doi.org/10.32479/ijeep.11787